Efficiency of using probiotic Elac-grow and Han-proway in laying-egg hens - Van, Dinh Thi Tuyet; Thi Thu, Nguyen; Hong Linh, Nguyen; Thi Men, Nguyen; Van Khanh, Tran; Nhi Cong, Le Thi (Vietnam Journal of Biotechnology, 2022)
Industrial chicken farm has to face many challenges such as epidermis and environmental pollution. Antibiotics and synthetic antimicrobial agents are routinely used to alleviate stress as well as to elevate growth and feed efficiency. However, using antibiotic had many negative effects, especially antibiotic resistance; therefore, probiotic products are a bio-secure solution being popularly applied in livestock husbandry.  The study was carried out on the two probiotics   Elac-grow, a diet supplement, and Han-proway, a waste treatment product, in industrial egg-laying hens. There were two lodgings (test and control) in these experiments; each had 4000 23-week-old hens of Hyline breed. Two probiotics were applied to the test and none to the control. The results showed that there was not significantly difference of egg yield between the two groups, although, the test lodging had higher egg yield growing ratio (67.48%) than the control one (65.73%). Egg quality in the experimental lodging was also significantly improved in the damaged egg ratio, the egg weight and the egg yolk weight after using Elac-grow. The efficiency of using Elac-grow and Han-proway was also shown through the concentration of ammonia emission in animal lodging. The ammonia value of the test lodging was maximum 5 ppm and remained stable at this point, lower than of the control. This efficiency was shown significantly in the microbial fluctuation analysis, when the total bacteria and coliform counts were reduced in the test lodging sequentially above 1x108 CFU bacteria/g and above 1x107 CFU coliform/g, the control had uptrend sequentially above 2x109 CFU bacteria/g and above 1x108 CFU coliform/g.